1999
DOI: 10.1046/j.1523-1747.1999.00590.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum Xylosyltransferase: a New Biochemical Marker of the Sclerotic Process in Systemic Sclerosis

Abstract: UDP-D-xylose:proteoglycan core protein beta-D-xylosyltransferase (EC2.4.2.26) is the initial enzyme in the biosynthesis of chondroitin sulfate and dermatan sulfate proteoglycans in fibroblasts and chondrocytes. Secretion of xylosyltransferase into the extracellular space was determined in cultured human dermal fibroblasts. A more than 6-fold accumulation of xylosyltransferase activity in cell culture supernatant was observed (day 1, 0.6 microU per 106 cells; day 9, 4.1 microU per 106 cells); however, intracell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
75
1
3

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 77 publications
(85 citation statements)
references
References 30 publications
6
75
1
3
Order By: Relevance
“…XT-I activities in synovial fluid were found to be significantly increased in chronic inflammatory joint diseases (21). Furthermore, we detected elevated levels of XT-I in the sera of patients with systemic sclerosis and in the seminal plasma of infertile men (18,22,23). In previous studies, we could prove the existence of a gene encoding for XT-II in higher organisms.…”
mentioning
confidence: 58%
See 2 more Smart Citations
“…XT-I activities in synovial fluid were found to be significantly increased in chronic inflammatory joint diseases (21). Furthermore, we detected elevated levels of XT-I in the sera of patients with systemic sclerosis and in the seminal plasma of infertile men (18,22,23). In previous studies, we could prove the existence of a gene encoding for XT-II in higher organisms.…”
mentioning
confidence: 58%
“…Several investigations suggested that soluble glycosyltransferases were formed from membrane-bound enzymes by proteolytic cleavage between the catalytic and the transmembrane domain (37,38). We have shown that XT-I is secreted into the extracellular space together with proteoglycans (22,39), and that serum XT-I activity is a confirmed biochemical marker for the determination of fibrotic activity in systemic sclerosis (22,24).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We describe the development of a selective LC-MS/MS method for quantification of XT-I activity, a new fibrosis marker (6,21,22 ). The test is based on the binding of D-xylose to the synthetic peptide Bio-BIK-F, which was used as an acceptor for XT-I to form Bio-BIK-F-Xyl.…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal studies found that XT-I activity remained increased in the serum of scleroderma and SSC patients (6 ), a finding that corresponds to an increase of proteoglycan metabolism in sclerotic organs and the theory that XT-I is secreted simultaneously into the extracellular matrix with chondroitin sulfate containing proteoglycans (6 -8 ). Increased glycosaminoglycans have been found in patients with SSC, and the increased chondroitin sulfate and dermatan sulfate content in affected skin correlates with the severity of sclerotic skin (9 -11 ).…”
Section: © 2006 American Association For Clinical Chemistrymentioning
confidence: 99%